2010
DOI: 10.1038/hr.2010.93
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for renal artery stenosis and chronic kidney disease in Japanese patients with peripheral arterial disease

Abstract: The prevalence and risk factors for renal artery stenosis (RAS) and chronic kidney disease (CKD) are unclear in Japanese patients with peripheral arterial disease (PAD). To examine these issues, we performed renal angiography in 410 patients with PAD. Renal function and damage were assessed using the estimated glomerular filtration rate (eGFR) and urinary level of microalbumin (MA). Multiple logistic and multiple regression analyses were used to examine the relationships of potential risk factors with RAS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
2
11
1
Order By: Relevance
“…Yen CJ et al also showed that serum uric acid levels were associated with eGFR and decline in renal function in elderly Taiwanese subjects by longitudinal analysis [9]. In Japanese, hyperuricemia, hypercholesterolemia and diabetes are risk factors for CKD in peripheral arterial disease [19]. In the present study, there was weak relationship between eGFR and serum uric acid levels at baseline.…”
Section: Openly Accessible Atcontrasting
confidence: 45%
“…Yen CJ et al also showed that serum uric acid levels were associated with eGFR and decline in renal function in elderly Taiwanese subjects by longitudinal analysis [9]. In Japanese, hyperuricemia, hypercholesterolemia and diabetes are risk factors for CKD in peripheral arterial disease [19]. In the present study, there was weak relationship between eGFR and serum uric acid levels at baseline.…”
Section: Openly Accessible Atcontrasting
confidence: 45%
“…Indeed, we have shown previously that renovascular disease as defined by the presence of renal artery stenosis on angiogram or MRA, unequal kidney size or suggestive renal flow scans or renal failure with significant atherosclerotic vascular disease including CAD, PVD and CVA was the third common cause of CKD among elderly. 13 Kumukara et al 14 analyzed the prevalence of CKD among PVD. They performed renal angiography in 410 patients with PVD.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the lowest quartile of serum uric acid (referent), the multivariable odds ratio for quartiles 2-4, respectively, of CKD were 1.53, 2.16 and 4.67 in Appalachian adults [9]. In the Japanese population, hyperuricemia, hypercholesterolemia and diabetes were risk factors for CKD in peripheral arterial disease [18]. Iso et al reported that eGFR was negatively correlated with the change in serum uric acid [19].…”
Section: Discussionmentioning
confidence: 99%